FATIGUE LIFE ANALYSIS OF DIFFERENTIAL CASE OF ELECTRIC DRIVE ASSEMBLY BASED ON ACTUAL LOAD SPECTRUM (MT) - ZOU XiHong; GOU LinLin; XIONG Feng; WANG Chao; JIANG MingCong; LIN YuQiang; WANG WanYing (Jixie qiangdu)
A method for the fatigue life analysis of the differential housing of the electric drive assembly based on the measured load spectrum is proposed. Taking the housing of an electric drive assembly differential of an electric vehicle as the research object, a finite element model of the housing is established, modal analysis is carried out, and modal test verification is carried out. On this basis, with the measured load spectrum of the differential housing as the load input, and the actual vehicle driving conditions as the boundary constraints, the dynamics simulation analysis of the differential housing is carried out. Based on the dynamic finite element analysis results of the differential housing of the electric drive assembly, the nominal stress method and the modified S-N curve of the housing, the fatigue life of the differential housing of the electric drive assembly is analyzed and researched. The results show that the fatigue failure position of the differential housing is consistent with the fatigue failure position during actual driving. Based on the actual driving load spectrum, the actual driving fatigue life of the differential housing can be accurately analyzed.